ҚАРАҚАЛПАҚ ШЕШЕНЛИК СӨЗЛЕРИНИҢ ЛИНГВОКОГНИТИВЛИК ҲӘМ ПРАГМАТИКАЛЫҚ ӨЗГЕШЕЛИКЛЕРИ - Оразов, Адилбай Орынбаевич (FAN va JAMIYAT, 2026)
The article analyzes the semantic, stylistic, and pragmatic properties of Karakalpak oratorical speeches (sheshenlik sozler) on a scientific basis. Using specific folklore examples, it reveals the cognitive nature of didactemes, which perform an educational function, and the role of allusions containing implicit references to historical and religious concepts. The stylistic role of euphemisms, reflecting the moral culture of the people and the level of linguistic politeness in oratorical prose, is determined. The research results contribute to a deeper understanding of the linguacultural content of the national oratorical tradition.